Introdução /Introduction - Gomes, Fernando (2019)
INTRODUCTION Freeing itself from the domain and dependence on traditional cartographies of knowledge, the publication of the first volume of Studies of Literature of the Centre for the Study of Letters (CEL-UÉ), entitled Landscapes of the Self, crosses epistemological frontiers and research practices. Landscapes of the Self are understood within this context as the narrative, dramatic or lyrical forms which the authors from all centuries and nationalities used to create characters and contexts which, in one way or another, represent individuals and societies. The adoption of different critical approaches aims at giving visibility to works in the field of Literature and Culture which discuss identity, memory, power or representation, among others, in several contexts and in diverse social and cultural periods, ranging from the public to the private realm, and to the several spaces and places of intimacy or exteriority and otherness, giving voice to the multiplicity and heterogeneity of the research work developed in CEL-UÉ. In the diversity of the Landscapes of the Self, to which the articles bear witness, two themes are the cornerstones of the volume: the exterior and the interior landscapes. The city, in its varied figurations is, par excellence, the physical landscape, if not the favourite, the one that has most inspired the artists, especially since the nineteenth-century. Fernando Gomes, analysing some authors throughout the centuries, recalls the origins of the myth of the perverse city in opposition to the city of perfection, highlighting the literary functions of that confrontation, as well as the ambivalence of man before his Creation. London, namely the ways the city is represented as a location of Power in private, social and political contexts in the two volumes of the political autobiography of Margaret Thatcher The Path to Power and The Downing Street Years, is the theme of the article co-authored by Ana Clara Birrento and Olga Gonçalves. In a methodological collaboration between critical agendas of cultural studies and discourse analysis, the article maps the city in its intersection between an axis of subjectivity and the logic of State Power. Moving South, to the Mediterranean landscapes, Odete Jubilado develops a comparative analysis around the short narratives Lettres de mon Moulin by Alphonse Daudet and Gente Singular by Manuel Teixeira Gomes, stressing the way these authors share their memories of Provence and the Algarve. The Island of Malta is in O Mistério da Estrada de Sintra, the scenery of a story of love and crime. Ana Luísa Vilela argues that through this narrative, Eça de Queirós contributed to the formation of an image of Malta, similar to the romantic woman, disturbing, seductress and unpredictable. The African landscapes are Centro de Estudos em Letras (CEL-UÉ) 12 the scenery of Onitsha by Le Clézio and Um rio chamado tempo e uma casa chamada terra by Mia Couto. Celina Martins writes about the way these narratives stage the initiation journeys of the protagonists into an Africa conceived as a space of transcendence, initiation and openness to the Other. The interior landscapes influenced, positively or negatively, by the environment that surrounds us, are a never-ending source of literary creation. On the one hand, the satirical tradition started by Horatio – production of his satire while he walks in the city – is the inspiration of the enunciator of the poems by Nicolau Tolentino. Carlos Nogueira shows that through an unstable laughter, the Tolentinian I-poet-character deconstructs the moral and behavioural models of the whole society of his time. On the other hand, Antero de Quental’s poetry reveals a closed and dialectal play of images and thoughts. Emphasizing the negativity and its most representative images, António Cândido Franco tries to show that the poetry of Quental is expression and landscape of a complex of metaphysics, able though to be solved by a superior unity of all the contraries. Crete is the geographical place, but also an intimate landscape, a mythic and literary place explored by Jorge de Sena in his poem “Em Creta, com o Minotauro”. Elisa Nunes Esteves re-reads this text, considered a hymn to Crete, pointing out the themes of identity, of the relation with motherland and exile idealized by the lyrical I. “To be or not to be Ophelia” that is the question put by Carla Ferreira de Castro, who reads Shakespeare’s verses through several lenses from other different artistic moments. Her article shows a double perspective of landscape, the geographical – the stream Ophelia chooses as her shroud -, and the psychological which corresponds to the essence of the young orphan girl unable to coexist with the successive losses she experiences. The representation of the Self and the Other in the literature of the nineteenth-century is the theme presented by Ana Cláudia Salgueiro da Silva, who analyses two novels, Uma Família Inglesa by Júlio Dinis and O Primo Basílio by Eça de Queirós, authors who through plural visions offer a distinct vision of the real with a pedagogic aim, namely the consolidation of core social structures like marriage. The intricacies of feeling and of interiority, and the way the confrontation with society determines the wanderings along the diegesis by the protagonists of Eurico, o presbítero and Ivanhoe are the object of the comparative reading of Teresa Mendes, who tries to understand the narrative and textual mechanisms found by Alexandre Herculano and Sir Walter Scott to construct their characters. This first volume of Studies of Literature of the Centre for the Study of Letters (CEL-UÉ), entitled Landscapes of the Self, is a collection of articles which postulate critical thought on diverse discursive modes – narrative, dramatic and lyrical texts – which, due to their multiplicity, bear witness to the vigour and contemporaneity of the literary representation of the world of the individuals. The volume was only possible due to the inestimable collaboration of the Scientific Committee, composed of : Estudos de Literatura: Paisagens do Ser / Landscapes of the Self 13 Ana Isabel Moniz (Universidade da Madeira) Antonio Sáez Delgado (Universidade de Évora) Cristina Robalo Cordeiro (Universidade de Coimbra) Elisabeth Jay (Oxford Brookes University) Helena Buescu (Universidade de Lisboa) Jeanyves Guérin (Université Sorbonne-nouvelle – Paris III) José Pedro Serra (Universidade de Lisboa) Mário Avelar (Universidade Aberta) Fernando Gomes Ana Clara Birrento Odete Jubilado Elisa Nunes Esteves